2022
DOI: 10.1038/s41598-022-11745-0
|View full text |Cite|
|
Sign up to set email alerts
|

Foot–ankle therapeutic exercise program can improve gait speed in people with diabetic neuropathy: a randomized controlled trial

Abstract: This study sought to determine whether a foot–ankle therapeutic exercise program can improve daily physical activity (i.e. number of steps) and fast and self-selected gait speed in people with diabetic peripheral neuropathy (DPN). In this single-blind randomized controlled trial and intention-to-treat analysis, 78 volunteers with DPN were allocated into a control group, which received usual care, and an intervention group (IG), which received usual care plus a 12-week foot–ankle exercise program. The adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 63 publications
1
34
0
4
Order By: Relevance
“…In the present study, ankle ROM increased both in plantar- and dorsiflexion directions. A research study found similar results, where ankle dorsiflexion improved after a 12-week foot-ankle training carried out on a solid surface [ 17 ]. However, this training consisted a 2 + 2 times per week supervised and digitally supervised home-based program, 50 min per session.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present study, ankle ROM increased both in plantar- and dorsiflexion directions. A research study found similar results, where ankle dorsiflexion improved after a 12-week foot-ankle training carried out on a solid surface [ 17 ]. However, this training consisted a 2 + 2 times per week supervised and digitally supervised home-based program, 50 min per session.…”
Section: Discussionmentioning
confidence: 64%
“…Studies targeting improvements in ankle range of motion (ROM) found inconsistent results, showing no change after home-based stretching [ 8 ], but a favorable change after a supervised program [ 17 ]. The case was the same in studies investigating the effects of balance training; there was no improvement in balance after a home-based intervention [ 18 ], but supervised balance training programs improved balance [ 19 ] or developed transfer in walking ability [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…With mixed outcomes reported in the various RCTs, 6 and new RCTs published since our previous systematic review (e.g., 9,10 ), a systematic review and meta-analysis of all studies and outcomes published to date is required to advance our understanding of the clinical and biomechanical effectiveness of foot-ankle exercise programs in people with diabetes-related neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this review was the predefined set of interventions which excluded studies that used gait training 50,51 or functional training 52 as an intervention. Similarly, our limited set of outcome measures excluded articles that measured improvements in physical activity, 53 foot ulcer incidence 54,55 and neuropathy signs. 52,53 However, the purpose of this review was to inform the intervention design of a proof-of-concept RCT which investigated the effects of mobilisations combined with stretches on ankle ROM, PPPs and balance.…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, our limited set of outcome measures excluded articles that measured improvements in physical activity, 53 foot ulcer incidence 54,55 and neuropathy signs. 52,53 However, the purpose of this review was to inform the intervention design of a proof-of-concept RCT which investigated the effects of mobilisations combined with stretches on ankle ROM, PPPs and balance. 56 Lastly, the effects of exercise interventions on balance in people with diabetes have not been investigated.…”
Section: Limitationsmentioning
confidence: 99%